Developing a Treatment-Resistant Depression Consultation Program, Part I: Practical and Logistical Considerations - Voytenko, Vitaliy L; Conroy, Susan K; Docherty, Anna R; Burnett, Diana K; Quevedo, Joao; Flood, Michael J; Riva Posse, Patricio; Virk, Subhdeep; Wright, Jesse H; Bobo, William V; Fournier, Jay C; Parikh, Sagar V (The journal of clinical psychiatry, 2025)
To provide recommendations for creating and sustaining a treatment-resistant depression (TRD) consultation program at an academic health center. This is a complementary manuscript to Part II, which discusses critical elements of the assessment package for such subspecialized consultations. Participants were a working group of 12 clinicians, researchers, administrators, and patient advocates from the National Network of Depression Centers (NNDC) TRD Task Group. The recommendations are based on expert opinion. TRD consultation programs can offer an individualized treatment roadmap to be implemented by the patient and their providers with the goal of maximizing the likelihood of response or full remission of symptoms. However, there is currently no published work addressing the practical and logistical considerations for establishing such programs. This consensus statement puts forth a set of recommendations that could serve as a basis for future empirical work. Members of the working group provided written descriptions of relevant procedures used at their institutions, which were used during a day-long in-person forum to achieve consensus on recommendations for each major aspect of a TRD consultation program. Subgroups were formed to draft recommendations, and points of disagreement were resolved at subsequent meetings of the full working group. We describe key practical considerations, including systems-level and financial issues; equity and access to TRD care for a diverse patient population; selecting a target population and facilitating the referral process; the product of the consultation; communication between the program, patient, and community providers; and postconsultation care and contact.